Theoretical and methodological approach to the competitiveness of enterprises - Bielienkova, O.Yu.; Molodid, O.O.; Gavrilyuk, V.Ya (Ways to Improve Construction Efficiency, 2022)
In the article, the analysis of theoretical approaches to the formation of the concept of "competitiveness of the enterprise" and the definition of methodical approaches to the assessment of the level of competitiveness of the enterprise of the healthy and the budvelous enterprise of the zocrema are analyzed. The review of literature sources allowed to identify the main problems that need to be addressed for proper methodological support of competitiveness management of construction companies, namely: substantiation of a set of diagnostic indicators and development, testing and bringing to specific guidelines algorithmic sequence of diagnostic procedures based on diagnostic procedures. In addition, the methodological security of managing the competitiveness of businesses in everyday life can aggregate the most successful and efficient warehouses of the most important scientific and applied developments, thus confirming their effectiveness in managing businesses of other types of activities. Therefore, using the method of forming a methodological basis for evaluating the level of the building capacity of business enterprises to save competitiveness, we analyzed it with a further systematization, first indicators for evaluating competitiveness and methods of recruitment in the city. Second, groups of methods for assessing the competitiveness of enterprises were classified. A number of indicators have been identified that allow assessing and determining the level of competitiveness of a construction company (such as increasing the rate of renewal of the active part of fixed assets, reducing the duration of working capital, increasing productivity, increase in the level of return on wages, reduce the level of current costs per unit of marketable products, increase the level of product quality, return on investment, total cost of production resources per unit of output, profitability (profitability) of products, equity, payback period, etc.) allows to assess the level of competitiveness of the construction company.